STUDENTS’ SATISFACTION TOWARDS ONLINE LEARNING DURING THE COVID19 PANDEMIC THROUGH END-USER COMPUTING SATISFACTION (EUCS) - Wahyuni; Siti Habsari Pratiwi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The Covid-19 pandemic has brought significant changes to learning systems. Thus, it is highly important to evaluate the implementation of online learning. This study aimed to investigate students’ satisfaction with online learning through End-User Computing Satisfaction (EUCS) proposed by Doll. There were five EUCS indicators utilized to determine the level of satisfaction, namely: content, accuracy, format, ease of use, and punctuality. EUCS instruments were adopted, modified, and tested for the validity of 12 items. This study involved 108 respondents consisting of students from four faculties at IAIN Langsa. Data were collected by using a google form questionnaire. The findings showed that the score for the indicator of the content of online learning was 67% (satisfied) while the score for the indicator of the accuracy of online learning was 54, 54% (quite satisfied). Moreover, the score of the indicator of the form of online learning was 56, 48% (quite satisfied), and the score of the indicator of the convenience of the access of online learning was 78, 79% (satisfied). At last, the score of the indicator of punctuality of online learning was 64, 26% (satisfied). This data showed that the highest score of students’ satisfaction was the convenience of the access of online learning while the lowest score of students’ satisfaction was the indicator of accuracy.